2021
DOI: 10.1098/rspa.2021.0585
|View full text |Cite
|
Sign up to set email alerts
|

Rogue waves in the three-level defocusing coupled Maxwell–Bloch equations

Abstract: The coupled Maxwell–Bloch (CMB) system is a fundamental model describing the propagation of ultrashort laser pulses in a resonant medium with coherent three-level atomic transitions. In this paper, we consider an integrable generalization of the CMB equations with the defocusing case. The CMB hierarchy is derived with the aid of a 3 × 3 matrix eigenvalue problem and the Lenard recursion equation,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…Nonlinear partial differential equations (NLPDEs) are the significant models to study many nonlinear phenomena in modern mathematical physics. With the development of modern mathematics and physics, the exact solutions of NLPDEs, especially some high-dimensional NLPDEs [1,2], have become a hot topic for scholars. Integrable systems and soliton solutions have also been extensively studied in the field of NLPDEs [3].…”
Section: Introductionmentioning
confidence: 99%
“…Nonlinear partial differential equations (NLPDEs) are the significant models to study many nonlinear phenomena in modern mathematical physics. With the development of modern mathematics and physics, the exact solutions of NLPDEs, especially some high-dimensional NLPDEs [1,2], have become a hot topic for scholars. Integrable systems and soliton solutions have also been extensively studied in the field of NLPDEs [3].…”
Section: Introductionmentioning
confidence: 99%
“…Because of the underlying integrability, it was found that Peregrine soliton can be extended to higher order exact rogue wave solutions in many nonlinear wave systems such as the NLS equation, [10][11][12][13][14] the derivative NLS equation, [15][16][17][18] the Sasa-Satsuma equation, [19][20][21] the Manakov equations, [22][23][24][25] the long-wave-short-wave equations, [26][27][28][29] the three-wave resonant interaction equations, [30][31][32][33][34] the Davey-Stewartson equations 35,36 and many others. [37][38][39][40][41][42][43][44][45] These analytic rational solutions with the higher order polynomials also represent the localized structure in both space and time coordinates, and could possess multiple intensity peaks or higher peak amplitudes. In particular, differing from the scalar system, the coupled and vector integrable systems with the additional degrees of freedom could allow the novel counterpart of rogue wave such as dark and four-petaled types.…”
Section: Introductionmentioning
confidence: 99%
“…From the mathematical description, Peregrine soliton characterized by a kind of rational solutions for the focusing nonlinear Schrödinger (NLS) equation was discovered to act as the prototype of realistic rogue waves, 9 as it exhibits the local wave structure in temporal–spatial plane and the height of maximum peak at the center reaches to three times the finite background. Because of the underlying integrability, it was found that Peregrine soliton can be extended to higher order exact rogue wave solutions in many nonlinear wave systems such as the NLS equation, 10–14 the derivative NLS equation, 15–18 the Sasa–Satsuma equation, 19–21 the Manakov equations, 22–25 the long‐wave–short‐wave equations, 26–29 the three‐wave resonant interaction equations, 30–34 the Davey–Stewartson equations 35,36 and many others 37–45 . These analytic rational solutions with the higher order polynomials also represent the localized structure in both space and time coordinates, and could possess multiple intensity peaks or higher peak amplitudes.…”
Section: Introductionmentioning
confidence: 99%
“…But for any given nonlinear partial differential system, it is almost impossible to find all of its solutions [1][2][3]. However, by applying the symmetry theory to NPDEs, some exact solutions that keep certain transformations invariant can be obtained by the lowering of the dimension of the equations [4,5], which is also called the optimal system problem. For one dimensional optimal systems, its construction was first proposed by Ovisiannikov, who used the ensemble matrix of the adjoint representation [6].…”
Section: Introductionmentioning
confidence: 99%